2011
DOI: 10.3892/ijmm.2011.778
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of human osteoblasts for periprosthetic osteolysis following exposure to wear particles

Abstract: Abstract. Aseptic loosening in total hip replacement is mainly caused by wear particles inducing inflammation and osteolysis. Wear can be a consequence of micromotions at the interface between implant and bone cement. Due to complex cellular interactions, different mediators (e.g. cytokines, proteinases) are released, which can promote osteolytic processes in the periprosthetic tissue followed by loosening of the implant. Furthermore, a reduced matrix synthesis and an induced apoptosis rate can be observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(116 citation statements)
references
References 40 publications
9
103
0
1
Order By: Relevance
“…In inflammatory conditions, this balance is altered. In response to wear particle stimulation, osteoblast ability to secrete osteoid is impaired [41], and collagen I synthesis is decreased [46]. Additionally, wear particles induce production of IL-1, IL-6, IL-8, TNF-a, CCL2, and MMP1 in osteoblasts [41,46], in addition to osteoclastogenesis factors, RANKL and M-CSF [47].…”
Section: Implant-induced Inflammatory Complicationsmentioning
confidence: 99%
“…In inflammatory conditions, this balance is altered. In response to wear particle stimulation, osteoblast ability to secrete osteoid is impaired [41], and collagen I synthesis is decreased [46]. Additionally, wear particles induce production of IL-1, IL-6, IL-8, TNF-a, CCL2, and MMP1 in osteoblasts [41,46], in addition to osteoclastogenesis factors, RANKL and M-CSF [47].…”
Section: Implant-induced Inflammatory Complicationsmentioning
confidence: 99%
“…Perfluorodecalin and bone regeneration It should also be remembered that halogenated decalins such as PFD can be partially brominated, increasing their radiopacity even further with little change in toxicity and physical properties (Long et al, 1971;Long et al, 1975;Lowe, 1991;Mattrey et al, 1987;McFarland et al, 1985).…”
Section: F Tamimi Et Almentioning
confidence: 99%
“…Since the pH of the cell culture media was maintained at neutrality throughout both experimental conditions, it is possible that differences in cohesion could have caused the significant differences in cell survival between the waterbased CPC and the PFD-based CPC. Indeed particle release from biomaterials has been found to have a negative effect on cellular survival in the surrounding tissues (Lochner et al, 2011). However, the effect of particle release from cements on cellular survival needs further investigation.…”
Section: Oxygen Delivery In Vitromentioning
confidence: 99%
“…The few studies investigating their role in bone formation show that peri‐prosthetic tissue cells produce factors that suppress osteoblast function and induce production of inflammatory cytokines 12, 13. Moreover, wear particles and metal ions can directly affect osteoblasts by reducing type one collagen production14, 15 and decreasing alkaline phosphatase activity as well as calcium deposition 16. In addition, wear particles have been shown to decrease osteoblast proliferation,15, 17 change the phenotype of mature osteoblasts,18 and stimulate osteoblasts to secrete inflammatory cytokines 14, 15, 16, 19.…”
mentioning
confidence: 99%
“…Moreover, wear particles and metal ions can directly affect osteoblasts by reducing type one collagen production14, 15 and decreasing alkaline phosphatase activity as well as calcium deposition 16. In addition, wear particles have been shown to decrease osteoblast proliferation,15, 17 change the phenotype of mature osteoblasts,18 and stimulate osteoblasts to secrete inflammatory cytokines 14, 15, 16, 19. Remarkably, one study revealed that cells from the peri‐prosthetic tissue produce several osteoblastic proteins themselves 20.…”
mentioning
confidence: 99%